Mutant p53 and MDM2 in Cancer - Deb, Swati Palit.; Deb, Swati Palit.; Deb, Sumitra.; Deb, Sumitra. (Subcellular Biochemistry, 2014)
This book provides the readers with an overview of research on p53, which has been shown to play a role in numerous crucial biological pathways in normal and cancer cells. Leading scientist in the field, who have all made direct contributions to the understanding of the molecular events underpinning p53 function, have been invited to contribute the various chapters, which discuss the current knowledge of the signaling cascades that are activated by mutations in p53 and overexpression of MDM2, frequently found in human cancer, and are major causes of oncogenesis. This book features chapters on the molecular basis of oncogenesis induced by gain of function mutation of p53, signaling pathways induced by MDM2 overexpression, control of mutant or wild-type p53 function by MDM2 and MDMX, p53 mutation in hereditary cancer, and structural aspects that activate mutant p53 which can be targeted by drug therapy. This book should be useful for scientists at all levels.